2017
DOI: 10.1115/1.4036465
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Analysis of Origami-Inspired Vibration Isolator With Quasi-Zero-Stiffness Characteristic

Abstract: We present a prototype vibration isolator whose design is inspired by origami-based foldable cylinders with torsional buckling patterns. The vibration isolator works as a nonlinear spring that has quasi-zero spring stiffness in a given frequency region, where it does not transmit vibration in theory. We evaluate the performance of the prototype vibration isolator through excitation experiments via the use of harmonic oscillations and seismic-wave simulations of the Tohoku-Pacific Ocean and Kobe earthquakes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The results revealed that the intra and inter‐well dynamics of the bistable stacked Miura‐ori are strongly influenced by the asymmetry in its force‐deformation relationship. A cylindrical truss structure inspired by the Kresling folding pattern were investigated for vibration isolation both numerically and experimentally . This vibration isolation function stemmed from a quasi‐zero stiffness (QZS) property obtained by integrating a linear spring with the bistable Kresling pattern.…”
Section: Folding Induced Mechanical Propertiesmentioning
confidence: 99%
“…The results revealed that the intra and inter‐well dynamics of the bistable stacked Miura‐ori are strongly influenced by the asymmetry in its force‐deformation relationship. A cylindrical truss structure inspired by the Kresling folding pattern were investigated for vibration isolation both numerically and experimentally . This vibration isolation function stemmed from a quasi‐zero stiffness (QZS) property obtained by integrating a linear spring with the bistable Kresling pattern.…”
Section: Folding Induced Mechanical Propertiesmentioning
confidence: 99%
“…After substituting Equations (11) and (12) into Equation (7), the axial force produced by face 2 and face 3 is given as:…”
Section: Magnetization Directionmentioning
confidence: 99%
“…It was found that the QZS system could produce a smaller dynamic stiffness in larger displacements near the equilibrium position, which helps to improve the performance of vibration isolation. In Ishida et al [11], a vibration Appl. Sci.…”
Section: Introductionmentioning
confidence: 97%
“…It can be assembled easily from a single sheet-like origami, and properties like rigidity, bistability and energy curves can be adjusted based on the number of corners and the angles of the folding pattern. Cylindrical origami has already been used successfully as a functional mechanism for memory and as a damper [3]. It is bistable-its two stable states are when the twist in the cylinder is either unfolded or folded-and can transmit signal by sequentially causing folding transitions from one unit to the next as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%